(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The aim of this research is to assess and quantify the impacts of leveraging artificial intelligence (AI) applications on enhancing the quality benchmarks in online higher education programs in the kingdom of Saudi Arabia. Specifically, the study will survey a sample of 200 instructors and students involved in the online education process to evaluate their perceptions of how AI-enabled functionalities influence key quality indicators. This research follows a quantitative methodology to meet the core research objectives of assessing the impacts of AI adoption on online education quality. The target population encompasses all students and instructors engaged in remote higher education programs across universities in Saudi Arabia. Based on sample size power calculations, a sample of 200 participants will be recruited, including both undergraduate and graduate-level students enrolled in fully online degree courses as well as instructors directly responsible for teaching remote classes. The findings of the research revealed that a Pearson Correlation of 0.784 and a p-value of 0.039 (less than significance level of alpha=.05) suggests a significant positive association between AI Applications and the Quality of Online Higher Education provided by teachers. And a Pearson Correlation of 0.861 and a p-value of 0.022 (less than significance level of alpha=.05) suggests a significant positive association between AI Applications and the Quality of Online Higher Education for students.